Phase formation and electrical properties of sodium bismuth titanate doped by barium titanate - Khairunnisa, Ibrahim (2017)
This thesis purpose is to define the phase formation and electrical properties of Sodium Bismuth Titanate Doped by Barium Titanate using various ratios. The BNT is a candidate material for future dielectric and piezoelectric applications that cover large temperature ranges. BNT based materials are being studied to create an alternative of PZT that can meet the current industry standard. The present work encompasses the structural, microstructural, functional group, density and impedance analysis on BNT lead-free ceramics synthesized in the frequency range 1 kHz-30 MHz. Powder X-ray diffraction pattern derived from the resulting data at the room temperature subjected to Rietveld refinements and Williamson-Hall plot analysis confirmed the formation of phase pure compound. The FESEM micrograph images of the samples showed dense microstructure and uniform grain size. Fourier Transform Infrared Spectroscopy related to the change of dipole moment and the possible of transition of energy levels. Then, Archimedes Principles testing showed the porosity present in the pallets and last, Impedance Analysis plots showed the dielectric constant (ε’) and dielectric loss (tan δ) decreased as the frequency increased.